2018
DOI: 10.1590/s1980-6574201800010006
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes, healthcare expenditures and its correlation with anthropometric factors and physical activity: 18-month follow-up in a Brazilian city

Abstract: To compare the profile of adults attended at primary care level of the Brazilian National Health System according to occurrence of T2DM during 18 months of follow-up. Method: Longitudinal study carried out with 316 adults. T2DM and PA were assessed by questionnaires. Measurements of weight, height and waist circumference (WC) were also performed. Healthcare expenditures were based on the demand of services registered in medical records. Analysis of variance (ANOVA) with Tukey's post hoc test was used, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Inpatient expenditure was reduced by 17.4% (p = 0.035) for moderate-intensity weekly exercisers and 28.7% (p = 0.001) for high-intensity weekly exercisers. This conclusion is supported by previous literature such as Araujo et al (2018) [30] and Wang et al (2019) [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Inpatient expenditure was reduced by 17.4% (p = 0.035) for moderate-intensity weekly exercisers and 28.7% (p = 0.001) for high-intensity weekly exercisers. This conclusion is supported by previous literature such as Araujo et al (2018) [30] and Wang et al (2019) [33].…”
Section: Discussionsupporting
confidence: 91%
“…The same is true for people at high risk of cardiovascular disease [29]. Araujo et al (2018) [30] found a positive correlation between physical activity and medical expenses for diabetes in 316 elderly people in a Brazilian city who were followed for 18 months. Thirdly, the impact of physical activity (PA) on medical expenditure also has gender differences.…”
Section: Introductionmentioning
confidence: 89%
“…No ano de 2015, a hipertensão atingiu ~31,2% da população brasileira (44.526.201 pessoas) e foi responsável por ~1 milhão de reais em despesas diretas com saúde e ~7 milhões de reais com perda de produtividade por absenteísmo e mortes prematuras (STEVENS et al, 2018). Pesquisa realizada com adultos com idade ≥ 50 anos verificou que despesas médias anuais da atenção primária à saúde, para indivíduos com diabetes, foram ~ 1,39 vezes maior quando comparado aos indivíduos sem a doença (ARAUJO et al, 2018). Ademais, em 2011, despesas relacionadas à obesidade totalizaram US$ 269,6 milhões, o que correspondeu a 1,86% de todas as despesas com atendimento de média e alta complexidade no país (DE OLIVEIRA;SANTOS;DA SILVA, 2015).…”
Section: Resultsunclassified
“…Porém, ao final de 12 meses de participação no PAC, a diferença significativa entre os grupos não prevaleceu para P e IMC. Avaliando-se dados de UBS em Presidente Prudente (SP), após 18 meses, Araujo et al 25 concluíram que os participantes com DM2 e participantes que desenvolveram DM2 durante o acompanhamento, mostraram maiores valores de IMC, circunferência da cintura, gastos com saúde e foram menos ativos quando comparados aos participantes sem diagnóstico de DM2.…”
Section: Discussionunclassified